Sub-saharan African regional economy : Determinants of foreign direct investment and growth empirics - Eric, Olabisi Olabode (unimas, 2016)
The general economic situation in Sub-Saharan African countries and the aspirations of international organisations such as the World Bank, the World Trade Organization (WTO), and the United Nations Conference on Trade and Development (UNCTAD) have spurred much research interest on how the region can improve economically and achieve sustainable economic growth. This study aims to investigate the Sub-Saharan regional economy with a focus on determinants of foreign direct investment (FDI) and growth empirics. A panel data analysis of FDI determinants was done for a sample of 10 Sub-Saharan Africa (SSA) countries for a period of 1980 to 2011. The findings showed a long run cointegration among the variables examined. Moreover, trade openness, financial development, and human capital were found to be positive and significant in explaining FDI inflows to SSA region.